In situ TEM tensile testing of carbon-linked graphene oxide nanosheets using a MEMS device. (3rd June 2016) - Cao, Changhong; Howe, Jane Y; Perovic, Doug; Filleter, Tobin; Sun, Yu
Abstract: This paper reports in situ transmission electron microscopy (TEM) tensile testing of carbon-linked graphene oxide nanosheets using a monolithic TEM compatible microelectromechanical system device. The set-up allows direct on-chip nanosheet thickness mapping, high resolution electron beam linking of a pre-fractured nanosheet, and mechanical tensile testing of the nanosheet. This technique enables simultaneous mechanical and high energy electron beam characterization of 2D nanomaterials.